Serum uric acid in patients with abnormal thyroid functions: a cross-sectional study - Bhattarai, Kushal; Manandhar, Nilu (Journal of Chitwan Medical College, 2019)
Background: Hyperuricemia, a pathologic consequence of over-production or under-excretion of uric acid, is a common biochemical picture in thyroid dysfunctions. This study was designed to determine the serum uric acid levels and the prevalence rates of hyperuricemia in thyroid dysfunctions. Methods: A cross-sectional study was conducted at College of Medical Sciences and Teaching Hospital, Chitwan in which Serum uric acid concentrations of male and female participants, 30 years or older with the diagnosis of hypothyroidism or hyperthyroidism were estimated. Hyperuricemia was defined as uric acid levels >6.8mg/dL (males) and >6.0 mg/dL (females). Descriptive statistics using frequency with percentage and inferential statistics using parametric and non-parametric tests were used. Results: In the total 249 participants, the prevalence of hyperuricemia was 30.5% (32.9% in hyperthyroid and 26.1% in hypothyroid patients). Similarly, the mean serum uric acid levels in these patients was 5.46 ± 1.88mg/dL (5.60 ± 1.71 in hyperthyroid and 5.20 ± 2.13mg/dL in hypothyroid patients). Hyperuricemia was present in 32.6% of the female and 27.6% of the male patients. Likewise, the rate was 28.1% in 30–40 years old, 30.0% in 40–50 years old, 30.9% in 50–60 years old, and 32.8% in >=60 years old participants. There was no significant association between hyperuricemia and age or gender in overall participants and in participants of either of the two groups of thyroid dysfunctions (p>0.05). Conclusions: The reported prevalence of hyperuricemia in thyroid dysfunctions justifies the need of further studies to understand the causal relationship between thyroid status and serum uric acid.